Fundamental Rights in Nepal: A Liberal Democratic Perspective - Gautam, Dilli Raj (Pragnya Sarathi, 2026)
Fundamental rights represent constitutionally recognized human rights that initiate in the doctrine of natural law and have evolved along with liberal democratic constitutionalism. Grounded on classical philosophies of natural rights articulated by thinkers such as Locke and Rousseau, fundamental rights are premised on the inherent dignity, liberty, and equality of individuals, which pre-existed the state and obligate it to recognition and protection rather than creation. Liberal democracy, constitutionalism, and fundamental rights form mutually reinforcing pillars of the modern democratic welfare state, balancing individual autonomy with social control through the rule of law, representative institutions, and accountability. This article theoretically examines the interrelationship between liberal democracy and fundamental rights and traces their historical and constitutional development in Nepal. It reviews Nepal’s constitutional trajectory from the mid-twentieth century to the Constitution of Nepal 2015, highlighting shifts from autocratic rule to multiparty democracy, and federal republicanism. The progressive expansion of civil, political, social, economic, and cultural rights—including protections for certain groups and laws focused on social justice—is given special consideration. While the 2015 Constitution reflects core attributes of liberal democracy and significantly broadens the scope of fundamental rights, the article also underscores persistent challenges related to inclusiveness, social acceptance, and practical implementation amid economic constraints and geopolitical complexities. The study concludes that although Nepal’s constitutional framework symbolically aligns liberal democracy with an extensive catalogue of fundamental rights, the realization of these rights depends on effective institutional capacity, common political commitment, and equitable socio-economic transformation.